Dissolution method of aluminum from fly ash - ZHAO YUHANG; GUO ZHAOHUA; WANG LIANMENG; WANG QIRUI; ZHOU YONGLI; SUN GUOCAI; MIAO JIABING (2014)
The invention discloses a dissolution method of aluminum from fly ash. The method comprises the following steps of: S1, pretreating the fly ash; S2, adding a hydrochloric acid alcohol solution into the pretreated fly ash to carry out an acid dissolution treatment so as to obtain acid soluble products; S3, carrying out solid-liquid separation on the acid soluble products to obtain an alcohol solution of aluminum chloride; S4, evaporating the alcohol solution of aluminum chloride and carrying out solid electrolysis on obtained anhydrous aluminum chloride to obtain primary aluminum. The acid dissolution treatment and the solid-liquid separation are carried out on fluidized bed fly ash with higher reactivity by using the hydrochloric acid alcohol solution, then the alcohol solution of aluminum chloride can be obtained, the alcohol solution of aluminum chloride is evaporated to obtain the anhydrous aluminum chloride, and the anhydrous aluminum chloride is electrolyzed to obtain the primary aluminum. According to d